Harmful effects of cyanobacterial blooms in Lake Ludaš (Serbia) on Carassius gibelio tissues - Tokodi, Nada; Drobac Backović, Damjana; Marinović, Zoran; Sunjog, Karolina; Jovanović Marić, Jovana; Kolarević, Stoimir; Kitanović, Nevena; Vuković-Gačić, Branka; Lujić, Jelena; Svirčev, Zorica (Biologia Serbica, 2023)
Lake Ludaš is a protected nature reserve in Serbia that has been the focus of scientific interest, due to perpetual water quality deterioration that has led to consistent cyanobacterial blooms for almost five decades. To describe the possible effects of cyanotoxins on fish (Carrasius gibelio) inhabiting Lake Ludaš, several examinations were performed in November of 2018, including: assessment of water quality (physical and chemical parameters, as well as water microbiology), and assessment of several tissues of C. gibelio (micronucleus test, comet assay, and histopathological analyses). The water quality of Lake Ludaš has been categorized as class III, indicating moderate pollution. Physical and chemical parameters from November of 2018 seemed to be within acceptable levels. Examined fish tissues showed signs of DNA damage (highest in the blood, followed by the liver and gills), and histological alterations (in the liver and gills). Although other xenobiotics can induce similar changes, cyanotoxins could be the most likely cause of the observed alterations in C. gibelio tissues. The present study demonstrates the need to monitor this important wetland of international significance, since the living organisms in Lake Ludaš are showing signs of environmental stress suggesting that the preservation and natural balance of this ecosystem could be in danger.